The Constitutionality Of Open Legal Policy On The Guarantee Of Citizens Rights In Judicial Review - Rudatyo,; Firdaus, Sunny Ummul; Jati, Ri’dhollah Purwa (The journal of contemporary issues in business and government, 2021)
This study aims to analyze the constitutionality of the open legal policy on the guarantee of citizens' rights in a judicial review. The results showed that an open legal policy can be interpreted as a freedom for legislators to form legal policies (laws). There were at least 15 Constitutional Court Decisions that did not grant the petition on the basis of open legal policy considerations from 2005 to 2015. However, until the time the conception related to open legal policy in the Constitutional Court Decision did not have clear boundaries.